Giant non-traumatic arteriovenous malformation of the scalp - Hasturk, Askin; Erten, Fuat; Ayata, Tulu (Asian Journal of Neurosurgery, 2012)
Arteriovenous malformation (AVM) of the scalp is an uncommon entity. Its management is difficult because of its high shunt flow, complex vascular anatomy, and possible cosmetic complications. The etiology of scalp AVMs may be spontaneous or traumatic. Clinical symptoms frequently include pulsatile mass, headache, local pain, tinnitus; and less frequently, hemorrhage and necrosis. Selective angiography is the most significant diagnosis method. Surgical excision is especially effective in AVMs and the most frequently used treatment method. In this article, we discussed the clinical features and surgical management of scalp AVMs.
Keywords: Arteriovenous malformation; diagnosis; scalp; treatment